Determinasi Faktor Psikologik, Sosial Dan Finansial Pada Kepuasan Kerja Tenaga Edukatif Akademi Keperawatan Universitas Muhammadiyah Purwokerto - Dyah Supriatin; Hima Barima (Jurnal Ilmiah Manajemen Kesatuan, 2022)
Lecturers as educational staff have an important role in a university. The success of higher education is determined by the high performance of lecturers and the ability to carry out the duties of the Tri Dharma of Higher Education. Meanwhile, the performance of lecturers cannot be separated from satisfaction with the work they do. Job satisfaction as a form of emotional response from positive and negative attitudes that affect feelings, thoughts about a pleasant attitude and love of work so that it will create maximum performance of lecturers in carrying out tasks in the fields of teaching education, research and community service. There are many factors that influence job satisfaction including psychological, social and financial factors. This study aims to determine the effect of psychological, social and financial factors on job satisfaction of educative staff at the Muhammadiyah Nursing Academy in Purwokerto. The research method uses a quantitative survey approach and questionnaires are given to respondents, namely lecturers (educative staff). Data analysis using logistic regression analysis is expected to be able to see the most influential factors on lecturer performance by looking at the regression equation modeling. Keywords: psychological, social, financial factors, job satisfaction